Real-world experience of venetoclax target dosing with concomitant posaconazole in adult patients with acute myeloid leukemia - Freeman, Tracelyn; Habib, Alma; Huang, Ying; Kumar, Pooja S.; Waller, Allyson; Fleming, Megan; McMillan, Kelsey; Hartzler, Natalia; Behbehani, Gregory; Blachly, James S.; Blaser, Bradley W.; Borate, Uma; et al. (Frontiers in Hematology, 2025)
Venetoclax creates ongoing challenges when combined with posaconazole due to a known drug-drug interaction. Herein, we investigated the safety between venetoclax 100mg and 70mg when administered with posaconazole in acute myeloid leukemia in this single-center, retrospective comparative analysis. Primary safety endpoints were incidence/duration of cytopenias and incidence of tumor lysis syndrome during the first treatment cycle. A total of 113 patients received venetoclax 100mg while 32 patients received 70mg. Comparing venetoclax 100mg vs 70mg, no statistically significant differences were seen in grade 3 neutropenia (89.4% vs 84.4%, p=0.53), grade 4 neutropenia (88.5% vs 87.5%, p=1.0), median duration in days of grade 4 neutropenia (23 [range 1–105] vs 28 [range 1-81], p=0.35), grade 3/4 anemia (88.5% vs 84.4%, p=0.55), grade 3/4 thrombocytopenia (81.4% vs 87.5%, p=0.42), or tumor lysis syndrome (2.7% vs 6.3%, p=0.30). In adult patients with acute myeloid leukemia, a target dose of venetoclax 100mg with posaconazole may be a safe alternative. Further studies assessing dose optimization are warranted.